(untitled) (MAUSAM, 2016)
In the context of climate change, extreme weather events are emerging as a potential threat to food security and farmers livelihoods. Considerable proportion of the revenue is being spent in addressing the damages caused due to these intense events. Extreme precipitation (both flood and drought) and temperature are crucial in causing detrimental impact on crop yield and production. Particularly, the impacts of extreme events will be more in rainfed agriculture due to interannual precipitation variability over the growing season in terms of crop yield and yield quality. Several studies have forecasted its increased occurrence and estimated its impact on agricultural productivity. Nevertheless, field level operational strategies to address these risks are easily not accessible to men and women farmers in that specific context. Since these events are localized in geographical scale, decentralised approach in the framework of ‘preparedness and recovery’ is suggested to combat the loss of lives, livelihoods and assets of men and women farmers. In this backdrop, the paper suggests few simple practical decentralised strategies to support the vast majority of small holders in our country.